2012
DOI: 10.1177/0098628312437724
|View full text |Cite
|
Sign up to set email alerts
|

Master’s and Undergraduate Industrial/Organizational Internships

Abstract: Internships play a vital role in the education of master's and undergraduate-level industrial/organizational (I/O) psychology students, providing applied learning experiences in organizational settings under qualified supervision. This article presents results collected from surveys of organizational hosts and interns. It addresses locating sites for internships, ensuring an appropriate experience, and the responsibilities of organizational hosts. The authors describe the responsibilities of faculty and studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Assessments of the internship experience also may identify the skills employers find most valuable, that is, the skills that increase employability for recent graduates. Furthermore, our data (Shoenfelt, Kottke, & Stone, 2012), as well as the data from other evaluations of internships (e.g., Cannon & Arnold, 1998;D'Abate, 2010;Taylor, 1988), indicate that the internship experience itself is an effective mechanism for developing rewarding skills (e.g., interpersonal skills, organizational savvy, professionalism). Thus, successfully completing an internship in and of itself increases the rewarding skill set Hogan et al indicated is most central to employability.…”
supporting
confidence: 67%
See 4 more Smart Citations
“…Assessments of the internship experience also may identify the skills employers find most valuable, that is, the skills that increase employability for recent graduates. Furthermore, our data (Shoenfelt, Kottke, & Stone, 2012), as well as the data from other evaluations of internships (e.g., Cannon & Arnold, 1998;D'Abate, 2010;Taylor, 1988), indicate that the internship experience itself is an effective mechanism for developing rewarding skills (e.g., interpersonal skills, organizational savvy, professionalism). Thus, successfully completing an internship in and of itself increases the rewarding skill set Hogan et al indicated is most central to employability.…”
supporting
confidence: 67%
“…For example, accounting interns perceived internships as helpful for developing interpersonal skills (Beck & Halim, 2008), and undergraduate marketing majors found internships helpful in developing the ability to work with individuals from varied backgrounds (Cook, Parker, & Pettijohn, 2004). We (Shoenfelt et al, 2012) found that organizational savvy, interpersonal sensitivity, and professionalism, among other skills, were judged by both organizational hosts and interns to have increased significantly during the course of the internship for I-O master'slevel students. Other skills reported to have been developed in the internship that are related to rewarding might include integrity and time management (i.e., those who are unable to complete obligations on time are not rewarding to deal with).…”
Section: Internships Develop Interpersonal Skills Not Formally Taughtmentioning
confidence: 68%
See 3 more Smart Citations